Instantaneous efficacy of laser therapy in recurrent aphthous stomatitis: A clinical case series - Sarah Afaque; Ribhu Ganguly; Neeta Misra; Deepak Umapathy (Wolters Kluwer Medknow Publications, 2023)
Recurrent aphthous stomatitis (RAS) or ulcer (RAU) is a common disorder affecting 5% to 60% of examined adult patient groups, with a female predominance. In this article, we report a case series of five patients with recurring oral ulcers, experiencing intense episodes. They were subsequently treated with laser therapy. It was recorded that laser therapy caused an immediate improvement in pain and discomfort, with spontaneous healing of aphthous ulcers without any apparent side effects.